Young and intense: FoxP2 immunoreactivity in Area X varies with age, song stereotypy, and singing in male zebra finches - Thompson, Christopher K.; Schwabe, Fabian; Schoof, Alexander; Mendoza, Ezequiel; Gampe, Jutta; Rochefort, Christelle; Scharff, Constance (Frontiers in Neural Circuits, 2013)
FOXP2 is a transcription factor functionally relevant for learned vocalizations in humans and songbirds. In songbirds, FoxP2 mRNA expression in the medium spiny neurons of the basal ganglia song nucleus Area X is developmentally regulated and varies with singing conditions in different social contexts. How individual neurons in Area X change FoxP2 expression across development and in social contexts is not known, however. Here we address this critical gap in our understanding of FoxP2 as a link between neuronal networks and behavior. We used a statistically unbiased analysis of FoxP2-immunoreactivity (IR) on a neuron-by-neuron basis and found a bimodal distribution of FoxP2-IR neurons in Area X: weakly-stained and intensely-stained. The density of intensely-stained FoxP2-IR neurons was 10 times higher in juveniles than in adults, exponentially decreased with age, and was negatively correlated with adult song stability. Three-week old neurons labeled with BrdU were more than five times as likely to be intensely-stained than weakly-stained. The density of FoxP2-IR putative migratory neurons with fusiform-shaped nuclei substantially decreased as birds aged. The density of intensely-stained FoxP2-IR neurons was not affected by singing whereas the density of weakly-stained FoxP2-IR neurons was. Together, these data indicate that young Area X medium spiny neurons express FoxP2 at high levels and decrease expression as they become integrated into existing neural circuits. Once integrated, levels of FoxP2 expression correlate with singing behavior. Together, these findings raise the possibility that FoxP2 levels may orchestrate song learning and song stereotypy in adults by a common mechanism.